The Influence of Local Taxes, Regional Levies, Regional Assets, and Special Allocation Funds on Local Own-Source Revenue - Dina Aulia Safitri; Annathasia P Erasashanti (CV Putra Publisher, 2026)
This study aims to analyze the impact of Local Taxes, Local Fees, Revenues from the Management of Separated Local Assets, and Special Allocation Funds on Local Own-Source Revenue in regencies and cities in West Java Province for the 2022–2024 period. This study is motivated by the importance of optimizing Local Own-Source Revenue as an indicator of regional fiscal autonomy, given that revenue targets remain unmet in various regions. This study employs a quantitative approach using secondary data obtained from the West Java Provincial Central Statistics Agency. The research data covers 27 districts/cities during the 2022–2024 period. Data analysis was conducted using the Robust Least Squares (RobustLS) method with the assistance of the EViews 10 application to obtain estimates that are more robust against violations of classical assumptions found in the research model. The results of the study indicate that Local Taxes, Local Retributions, and Special Allocation Funds have a positive and significant effect on Local Revenue.